Laparoscopic heminephrectomy in paediatric duplex kidney : A case report. - Khan, Sarforaj Ali; Khan, Md Rokonuzzaman; Chowdhury, Md Moynul Hoque; Faisal, Ferdous Mahmud; Karmoker, Rajib; Debnath, Amit (Bangladesh Journal of Urology, 2023)
Duplex kidney is one of the most common anomalies of the urinary tract. Early detection has dramatically increased due to advance in technology of imaging to detect the anomalies during antenatal period; however, numbers of undiagnosed adult still exist. It may remain asymptomatic, but may cause repeated urinary tract infections or calculi. This case report presents a case of a 10-year-old female who had right sided duplex collecting systems. This patient has repeated symptoms throughout the years, referred to several medical specialties. Then ultrasonography and computed tomography showed that she had complete duplex collecting system on her right kidney. She was then undergone laparoscopic heminephrectomy on right side and removal of dilated rigjt ureter. Congenital anomaly of the urogenital system should be considered in patients with chronic infection. Multimodal imaging technique such as ultrasonography, computed tomography, or magnetic resonance imaging should be done to confirm the diagnosis especially before surgical management. Bangladesh J. Urol. 2023; 26(2): 118-121